(untitled) (International Journal of Engineering and Computer Science, 2018)
Mobile Ad-hoc network is a collection of nodes that dynamically connected together to form a network without using any fixed infrastructure. Mobile nodes are connected by wireless links to form an arbitrary topology. As it is infrastructure less network, the information or data packets are send between the nodes with the help of radio signals and each node act as routers. MANET aimed is to provide communication capabilities to areas where limited or no predetermined communication infrastructures exist. MANETs are vulnerable to malicious entities that aim to tamper and analyze data and traffic analysis by communication eavesdropping or attacking routing protocols. For security issue one solution is to use anonymous routing in the network that cannot be identified by any other nodes or attacker or observer. High Security and privacy in ad-hoc networks has been a major issue, while it comes in the field of defense and other such sensitive communications. Most of the communication system provides security in routing and data content. Anonymous communications should focus on anonymity in identity, location and route of the participating nodes. Anonymous communication between the Manet nodes are challenging as the nodes are free to move anywhere. No centralized node is there to monitor or to control the other nodes. Here the chance of attack from malicious nodes is high. Anonymous routing protocols are crucial in MANETs to provide secure communications by hiding node identities and preventing traffic analysis attacks from outside observers.